TINGKAH LAKU MENGUNYAH KERBAU MOA YANG DIBERI HIJAUAN LOKAL DI PULAU MOA KABUPATEN MALUKU BARAT DAYA - C. Ch. E. Latupeirissa; Bercomien J. Papilaya; Richo P. Lelloltery (Jurusan Peternakan Fakultas Pertanian Universitas Pattimura, 2020)
The objective of the present study was to examined the chewing behaviour of Moa buffalo fed on local forages. The experiment was analysed as Latin square 4 x 4, four treatments and four replicates. The treatments were A (combination of graas and aulumadam), B (grass and knumge, C (grass and weru leaves) and D (grass).Variables measured were chewing during eating (intake rate, chewing rate and efficiency) and chewing during rumination (ruminating rate, time spent ruminating per bolus, rumination efficiency, and regurgitation rate). The result show that intake rate was 31.78, 30.52, 31.99, 32.14 gram/minutes for treatmen A, B, C and D, respectively. Chewing rate (no.of chew/minutes) for A, B, C and D was 50.81, 53.95, 56.50, and 55,67, reapectively, and chewing efficiency (no.of chews/dry weight) was 0.23, 0.31, 0.21, and 0.35 for A, B, C, and D, respectively. Ruminating rate (no of bolus/minutes) was 1.16, 1.06, 1.26, and 1.34 for A. B, C and D, respectively. Ruminating efficiency (no. of chews/bolus) for A, B, C, and D was 37.70, 43.68, 36.48 and 36.24, respectively. Time spent ruminating per bolus was 1.14, 0.96, 0.82. and 0.75 minutes for A, B, C, and D, respectivly, and regurgitation rate (minutes) was 0.16, 0.89, 1.46, and 0.44 for A, B, C, and D, respectively. It can be concluded than Moa buffalo consume all forages with similar rate and efficiency, while chewing rate differ among the the treatments. Chewing rumination is similar among all forages.